Interplay Among the Oral Microbiome, Oral Cavity Conditions, the Host Immune Response, Diabetes Mellitus, and Its Associated-Risk Factors—An Overview - Negrini, Thais de Cássia; Carlos, Iracilda Zeppone; Duque, Cristiane; Caiaffa, Karina Sampaio; Arthur, Rodrigo Alex (Frontiers in Oral Health, 2021)
This review aimed to investigate the interplay between the oral microbiome, oral cavity conditions, and host immune response in DM. Moreover, it also aimed to investigate how DM related risk factors act in promoting or modifying specific mechanisms that could potentially perpetuate both altered systemic and oral conditions. Poorly controlled glycemic index may change the immune system of affected individuals and it is also associated with increased levels and frequencies of periodontal pathogens in the subgingival biofilm of individuals with DM. DM individuals may have an exaggerated inflammatory response, poor repair and bone resorption that aggravates periodontal disease. Increased levels of systemic pro-inflammatory mediators found in individuals affected with periodontal disease exacerbate insulin resistance. SARS-CoV-2 infection may represent an aggravating factor for individuals with DM. An association between oral cavity, COVID-19 and DM has not yet been demonstrated. DM individuals tend to have low salivary flow and a high prevalence of xerostomia. DM has also been associated to the development of lesions in the oral mucosa, especially potentially malignant ones and those associated with fungal infections. Obesity plays an important role in the induction and progression of DM. Co-affected obese and DM individuals tend to present worse oral health conditions. Decrease in HDL and, an increase in triglycerides bloodstream levels seem to be associated with an increase on the load of periodontopathogens on oral cavity. An important interplay among oral cavity microbiome, DM, obesity and hypertension has been proposed as the reduction of nitrate into nitrite, in addition to contribute to lowering of blood pressure, reduces oxidative stress and increases insulin secretion, being these effects desirable for the control of obesity and DM. The results of the studies presented in this review suggest the interplay among the oral microbiome, oral cavity conditions, host immune response and DM and some of the DM associated risk factors exist. DM individuals need to be encouraged and motivated for an adequate oral health care. In addition, these results show the importance of adopting multidisciplinary management of DM and of strengthening physicians-dentists relationship focusing on both systemic and on oral cavity conditions of DM patients.